Force generation and wing deformation characteristics of a flapping-wing micro air vehicle 'DelFly II' in hovering flight - Percin, M; Oudheusden, B W van; Croon, G C H E de; Remes, B (Bioinspiration & biomimetics, 2016)
The study investigates the aerodynamic performance and the relation between wing deformation and unsteady force generation of a flapping-wing micro air vehicle in hovering flight configuration. Different experiments were performed where fluid forces were acquired with a force sensor, while the three-dimensional wing deformation was measured with a stereo-vision system. In these measurements, time-resolved power consumption and flapping-wing kinematics were also obtained under both in-air and in-vacuum conditions. Comparison of the results for different flapping frequencies reveals different wing kinematics and deformation characteristics. The high flapping frequency case produces higher forces throughout the complete flapping cycle. Moreover, a phase difference occurs in the variation of the forces, such that the low flapping frequency case precedes the high frequency case. A similar phase lag is observed in the temporal evolution of the wing deformation characteristics, suggesting that there is a direct link between the two phenomena. A considerable camber formation occurs during stroke reversals, which is mainly determined by the stiffener orientation. The wing with the thinner surface membrane displays very similar characteristics to the baseline wing, which implies the dominance of the stiffeners in terms of providing rigidity to the wing. Wing span has a significant effect on the aerodynamic efficiency such that increasing the span length by 4 cm results in a 6% enhancement in the cycle-averaged X-force to power consumption ratio compared to the standard DelFly II wings with a span length of 28 cm.